2008
DOI: 10.1007/s10499-008-9231-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the timing of initial feeding on growth and survival of loach (Misgurnus anguillicaudatus) larvae

Abstract: The effects of delayed first feeding on growth and survival and starvation on the point-of-no-return of loach Misgurnus anguillicaudatus larvae were studied by evaluating morphometric characteristics under controlled conditions. Larvae began to feed exogenously at 3 days after hatching (DAH) and the PNR occurred between 9 and 10 DAH at 23 ± 1.0°C. The experimental design included a conventional feeding regime with initial feeding from 3 DAH as a control, delayed first feeding for 4, 5 and 6 DAH. Morphometric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…These trends were also observed by Mookerji and Rao (1999) in rohu and singhi. Exogenous feeding generally commences before the yolk is fully absorbed (Ghelichi et al 2010;Gisbert et al 2000Gisbert et al , 2004Haga et al 2014;Islam 2005;Kailasam et al 2007;Klimogianni et al 2011;Mookerji and Rao 1999;Peña and Dumas 2005;Shan et al 2008;Wang 2010;Yang 2007), as was also observed in the present study.…”
Section: Discussionsupporting
confidence: 80%
“…These trends were also observed by Mookerji and Rao (1999) in rohu and singhi. Exogenous feeding generally commences before the yolk is fully absorbed (Ghelichi et al 2010;Gisbert et al 2000Gisbert et al , 2004Haga et al 2014;Islam 2005;Kailasam et al 2007;Klimogianni et al 2011;Mookerji and Rao 1999;Peña and Dumas 2005;Shan et al 2008;Wang 2010;Yang 2007), as was also observed in the present study.…”
Section: Discussionsupporting
confidence: 80%
“…Larval rearing relies on providing adequate culture conditions to enhance feeding success, growth and survival from the onset of exogenous feeding and reduce starvation (Peña & Dumas ; Zhang, Wang, Hu, Fan, Cheung, Shin, Li & Cao ; Wang, Hu, Wang, Cheung, Shin & Cao ). Type of prey, size of prey, light intensity and water temperature were dominant factors that affected feeding response of Pacific red snapper larvae at first feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Loach ( Misgurnus anguillicaudatus ; Cypriniformes; Cobitidae) is a demersal freshwater teleost, widely distributed in China, Korea, Japan, and other countries in southeastern Asia [ 1 ]. The loach can be used as a traditional Chinese medicine or folk remedy for treatments of hepatitis, osteomyeitis, carbuncles, inflammations and cancers, as well as for patient’s recovery from debilities caused by various pathogens and aging [ 2 ].…”
Section: Introductionmentioning
confidence: 99%